Buffalo Bill on stage - Sagala, Sandra K. (University of New Mexico Press, 2008)
Between 1872 and 1886, before he achieved acclaim for his Wild West show, ""Buffalo Bill"" led a troupe of traveling actors known as a Combination across the country performing in frontier melodramas. Biographies of William Frederick Cody rarely address these fourteen rather obscure years when Cody honed the skills that would make him the world-renowned entertainer as he is now remembered. In this revision of her earlier book, Buffalo Bill, Actor, Sandra Sagala chronicles the decade and a half of Cody's life as he crisscrossed the country entertaining millions. She analyzes how the lessons h